Assessing accrual accounting implementation in Cianjur regency: An empirical investigation - Aditya Wira Dianto; Khoirul Aswar (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: This research aimed to analyse the effect of top management support, training and communication on the implementation of accrual accounting. Design/methodology/approach: The hypotheses of the study were tested using the survey data from 63 working unit in Cianjur Regency. The instrument for content and construct validity and reliability was tested. Then, the hypotheses were tested using Structure Equation Modelling (SEM) by SmartPLS 3.0. Finding: This study found that top management support and training have significant relationship with implementation of accrual accounting. Meanwhile, communication has no significant relationship with implementation of accrual accounting. Research limitations/implications: This study contributes to provide input into the adoption of Government Regulation No. 71 of 2010 in order to apply the rule of accrual accounting to the fullest, and to minimize errors in financial reporting with the identification of possible obstacles faced in implementing accrual accounting. This study recommended that, more factors such as consultant support, education level and project management support are needed to complement and improve financial reporting with implementation of accrual accounting. Originality/value: To the best of the researcher's knowledge, no study of Cianjur Regency has tested the impact of factor such as top management support, training and communication on implementation of accrual accounting.
Keywords: I28; M15; M48; 330; Implementation of Accrual Accounting; Training; Top Management Support; Communication